Application of the Welfare Quality® protocol in pig slaughterhouses of five countries - Dalmau, Antoni; Nande, Alexandre; Vieira-Pinto, Madalena; Zamprogna, Silvia; Di Martino, Guido; Ribas, Juliana C.R. [UNESP]; da Costa, Mateus Paranhos [UNESP]; Halinen-Elemo, Katri; Velarde, Antonio (Elsevier, 2016)
The objective of the present study is to assess the variability of the measures used in the welfare quality (WQ) protocol for pigs among slaughterhouses in five different countries and to propose alarm and critical thresholds for the calculation of scores for future development of an animal welfare certification scheme. The WQ protocol was applied in 52,468 pigs in 42 slaughterhouses in 5 countries (Portugal, Italy, Finland, Brazil and Spain). The welfare assessment started in the unloading area, where measures of general fear, thermoregulation, slipping and falling, lameness, sickness and mortality were taken. Concerning lairage, space allowance, drinking points, thermoregulation and mortality were considered, and the human-animal relationship was assessed by means of high-pitched vocalisations when pigs were moved from lairage to the stunning system. Finally, stunning effectiveness, skin lesions and presence of pneumonia, pleurisy, pericarditis and white spots on the liver were assessed in the stunning area and after slaughtering the animals. There was a large degree of variability among slaughterhouses for measurements made. For instance, the percentage of animals slipping ranged from 0.4% to 57%. Pigs with signs of recovery after stunning ranged from 0% to 90% and the percentage of carcasses that were severely damaged with skin lesions ranged from 0% to 48%. The data obtained can be useful to establish some thresholds for future uses of the WQ protocol. Electric stunning was associated with more animals recovering consciousness than from CO2.
Keywords: Animal welfare; Assessment protocol; Behaviour; Human-animal relationship; Pigs; Sus scrofa